Relationship between perceived exertion and repetitions performed to exhaustion at selected percentages of one-repetition maximum in apparently healthy adults - madlena, troy (My University, 1995)
The purpose of this study was to determine the average number of repetitions that could be performed at 40, 50, 60, and 70% of 1-repetition maximum (1 RM), and to assess rating of perceived exertion (RPE) values associated with each percentage. Ten men (X age = 48) and 10 women (X age = 49) volunteered for the study. Absolute strength was assessed for each exercise via 1 RM testing, while relative muscular endurance testing consisted of performing maximum repetitions at each percentage of 1 RM. In addition, RPE values were assessed after the 10th repetition on each exercise, at each percentage.
Keywords: Weight training - Physiological aspects